METALLOPHYSICS OF DETERIORATION DURING FRICTION SLIDING IN THE PRESENCE OF ABRASIVE MATERIAL - Dvoruk, V.I.; Kindrachuk, M.V. (Proceedings of National Aviation University (archive), 2005)
Suggested new physical conception of wearing charge surface.